2009
DOI: 10.1515/cclm.2010.047
|View full text |Cite
|
Sign up to set email alerts
|

Use of flow cytometry (Sysmex® UF-100) to screen for positive urine cultures: in search for the ideal cut-off

Abstract: Background: Cultures for urinary tract infections (UTI) constitute a large workload in the clinical microbiology laboratory, although up to 80% are usually negative. Several automated methods are available to screen urines for UTI, one being the flow cytometry-based Sysmex ᭨ UF-100. Methods: The performance of the UF-100 was evaluated over a 16-month period using urine culture as the reference method. Results: During this period, a total of 5356 urine samples were studied (469 children; 3229 women and 1658 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 15 publications
5
36
0
3
Order By: Relevance
“…Although these numbers are comparable to another recent study evaluating the UF-1000i (11), most studies have reported a percentage of negative culture samples around 70 to 80% (2,4,15,22). The organisms identified in our study correspond well with earlier published results (2,4,9).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although these numbers are comparable to another recent study evaluating the UF-1000i (11), most studies have reported a percentage of negative culture samples around 70 to 80% (2,4,15,22). The organisms identified in our study correspond well with earlier published results (2,4,9).…”
Section: Discussionsupporting
confidence: 91%
“…Considering these facts, it is no surprise that urine samples are the most frequently received specimens in many microbiology laboratories. Nevertheless, a high number of these urine cultures will not yield any bacteria at all, and percentages for negative urine cultures up to 80% have been reported (2,15). Since urine culture is a laborious procedure, a more cost-effective approach would have a large impact on laboratory economics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors believe a culture to be negative until a count of i10 5 c.f.u. ml 21 is reached (Manoni et al, 2002;Falbo et al, 2012), whilst others deem samples positive at 10 3 c.f.u.ml 21 (Brilha et al, 2010;Kim et al, 2007). Culture classification has previously been suggested to have a profound effect on the calculated performance of microscopy analysers.…”
Section: Discussionmentioning
confidence: 99%
“…Although generally not required in cases of acute, uncomplicated cystitis [4], urine culture is still considered as standard of care in pyelonephritis, pregnant women, and men. Not surprisingly, urine cultures are among the most frequent culture analyses performed in the clinical microbiology laboratory [5]. However, up to 80 % of urine samples are negative, resulting in considerable workload and consumption of resources [6].…”
Section: Introductionmentioning
confidence: 99%